Problems Memorizing Al-Qur'an Verses For Islamic Religious Education Students Uin Sjech M. Djamil Djambek Bukittinggi - Fitri Yulia; Yelfi Dewi; Charles Charles; Salmi Wati (International Journal of Education, Information Technology, and Others, 2026)
This research is motivated by the fact that the Al-Quran memorization program that has been set as one of the academic requirements at UIN Sjech M. Djamil Djambek Bukittinggi has not been optimally implemented. Although the program has been set to encourage students to memorize the Al-Quran, in reality there are still many students who experience obstacles in the process, both in terms of technical and non-technical abilities. This study aims to identify the forms of problems faced by students in memorizing the verses of the Al-Quran, especially for PAI students of the 2021 batch. This study uses a qualitative approach with field research. Data collection techniques were conducted through in-depth interviews and documentation. The main informants in this study were 2021 PAI students in their eighth semester who had problems memorizing verses from the Qur'an, as well as academic advisors as supporting informants. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results of the study found that the problems faced by students in memorizing the Qur'an can be divided into two factors, namely internal and external factors. Internal factors include a lack of mastery of makhrijul huruf and tajwid, impatience, dishonesty, lack of sincere intention, excessive ambition to add new memorizations, and laziness in muraja'ah. Meanwhile, external factors include changing mushafs, an unsupportive environment, and being distracted by other things outside of memorization activities.